Professional development for faculty in Uzbekistan - Coffelt, Tina A.; Koziel, Jacek A. (Frontiers in Education, 2025)
This ethnographic case study focuses on adult learners in a professional development grant program. The program applied the ADDIE model to train faculty in Uzbekistan to conduct research, write for academic audiences, and publish in top-tier academic journals. Agricultural and biosystems engineering and English faculty members at a US Midwest university forged an interdisciplinary partnership to virtually deliver a 5-month program to an initial cohort of 68 participants. Topics included research ethics, experimental and survey research design, and structure of scientific papers, among others. The pre- and post-tests objectively measured material covered in the curriculum. Post-test scores from 18 participants showed improvement (n = 11), no change, (n = 4), or lower scores (n = 3). Regardless, the granting agency was pleased with the implementation of the project. This manuscript informs future collaborators on successful procedures, such as training models and virtual delivery, and opportunities for improvement, including English language proficiency, eligibility standards, and emphasizing research ethics.